Спосіб зниження кидків струму в системі електричної тяги в аварійному режимі "зняття відновлення" напруги на струмоприймачі - Михаліченко, П.Є. (Електротехніка і електромеханіка, 2012)
Experimental and theoretical methods are employed to estimate influence of the current collector detachment-contact mode on electromagnetic processes in a DC electric train. It is proposed to use electric energy storage to reduce current surge at the moment of power supply recovery.